Heat tolerance in Thai rice varieties - Supansa Sukkeo (2018)
© 2017, Science Society of Thailand under Royal Patronage. All rights reserved. Rice yield reduction at high temperature is a serious problem in the tropics and is likely to worsen with climate change. Temperature-tolerant rice varieties would be highly desirable in areas at risk of extreme temperatures. This study evaluated 7 modern Thai rice varieties with a wet season planting on 1st July (Planting date 1 (PD1)), and 3 dry season plantings 9th January (PD2), 23rd January (PD3), and 6th February (PD4), in 2009. The mean minimum and maximum temperature to which the crop was exposed during the different phases of reproductive growth were 20.6–24.1°C and 33.3–36.9°C for the 30 days before anthesis, 22.1–24.4°C and 32.1–37.6°C at anthesis, 22.5–24.0°C and 34.3–37.5°C for the 30 days after anthesis. Grain yields of all the varieties were lower in PD2–PD4 than in PD1. The dry season yield depression separated the rice varieties into two classes: sensitive varieties with a dry season yield of about half of the wet season yield (SPT1, NP1, R258 and SKN1), and tolerant varieties which showed much less seasonal difference in yield (RD10, CNT1, and SPR1). Sensitive and tolerant varieties were also differentiated by the way in which the proportion of unfertilized spikelets, number of spikelets per panicle, and proportion of filled grain correlated with the temperature during the relevant period of development, with the tolerant varieties being less responsive to rising temperature than the sensitive varieties. This study demonstrates a range of heat sensitive and tolerance already in existence among modern Thai rice varieties. We found a complex physiology of the high temperature response of rice, in which grain yield may be adversely affected during panicle development, anthesis, and during grain filling. The genes and QTLs for heat tolerance may need to be separately identified.